Reporte de un caso: incisivo central único - ´Hernández, Jesús Alberto; Gardeazábal , Luis Ernesto (Revista Estomatología, 1993)
This article reviews the literature about con genital absence of teeth and its possible causes associatedwith problems or sistemic sindroms, emphasizing on the inherence patterns involved in the anomaly, with this it pretends to cause diagnostic acumen to recognize the dental anomaly relating its presence with systemic syndroms and evaluating other members of the family to discard the inheritan patterns. In addition it presents a clinical case of a pauent attended the pediatric dental clinic of the Estomatology Department Universidad del Valle (Cali-Colombia), with absence of temporal and permanent buds of the superior central incisive, its clinical management and the treatment courses.